Two-stage pretreatment with alkaline sulphonation and steam treatment of Eucalyptus woody biomass to enhance its enzymatic digestibility for bioethanol production. (1st November 2018) - Chu, Qiulu; Song, Kai; Bu, Quan; Hu, Jinguang; Li, Fuqiang; Wang, Jing; Chen, Xueyan; Shi, Aiping
Highlight: Two-stage pretreatment of alkaline sulphonation and steam treatment was performed. Alkaline sulphonation improved the degree of lignin removal/modification. The following steam treatment further enhanced cellulose accessibility. The two-stage pretreatment maximized sugar yield from raw biomass. Fermentable sugars were efficiently converted to ethanol. Abstract: This work proposed a two-stage pretreatment with alkaline sulphonation and steam treatment, and investigated its efficiency for converting Eucalyptus woody biomass to fermentable sugars and bioethanol. Comparing with steam pretreatment and subsequent sulphonation, this alkaline sulphonation-steam pretreatment improved carbohydrate recovery by maintaining a more neutral pH throughout the pretreatment process, while promoting the enzymatic digestibility of biomass through lignin removal and modification. Results showed that the alkaline sulphonation-steam pretreatment caused lignin removal of 69.37% and 120.28 mmol/kg acid groups incorporation into substrate, both of which could lead to significantly improved cellulose accessibility. About 80% of the sugars present in the original carbohydrate (cellulose and hemicellulose) were released, which could be recovered after pretreatment and enzymatic hydrolysis. The sugars released from enzymatic hydrolysis of substrate pretreated by alkaline sulphonation-steam pretreatment could be efficiently converted to ethanol, indicating that alkaline sulphonation-steam two-stage pretreatment is a promising pretreatment approach of lignocellulosic biomass for the production of biofuels.